ITILin käyttöönoton haasteet IT-palveluhallinnan kehittämisessä - Viljanen, Topi (2017)
IT service management has grown to be an important part of a successful or-ganization. Organizations need an efficient and powerful IT department that is not limited to working only with hardware and software installations. ITIL is a set of best practices that offers comprehensive process definitions for different tasks that produce services. ITIL is widely adopted and used by many organizations worldwide. ITIL helps organizations to manage processes so that they work without surprises. Better efficiency and quality help organizations to minimize the losses. ITIL is not a standard and does not define how to work on low level. It works on an abstract level so that all organizations must adopt it the way they see the best. The problems appear when the organization tries to adopt ITIL but does it wrong. It can cause more trouble if applied to an organization without under-standing it correctly. This paper will concentrate on the pros and cons of ITIL as a guideline of IT service management. ITIL is popular because it offers the best practices and bet-ter quality but on this paper the focus is on the negative side of it. It is im-portant to understand the problems that are known so they that can be missed and prevented. The conclusion of this paper is that ITIL does help organizations to improve the IT service management and in most cases it is better to follow ITIL than skip it. When following ITIL you should understand it before applying it to all process-es and understand how it should be applied to already known processes. ITIL should not be the only reason to make changes; it should be used as guidance for planning them. ITIL should not be the only reference as it does not contain everything. By planning the changes beforehand and working with ITIL, organ-izations should be able to benefit from using it.